Pathologies elicited by the gymnophallid metacercariae of Bartolius pierrei in the clam Darina solenoides - Cremonte, Florencia (2003)
Fil: Cremonte, Florencia. Centro Nacional Patagónico. Puerto Madryn. Chubut; Argentina